If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -9 = 75 Reorder the terms: -9 + 14x = 75 Solving -9 + 14x = 75 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 14x = 75 + 9 Combine like terms: -9 + 9 = 0 0 + 14x = 75 + 9 14x = 75 + 9 Combine like terms: 75 + 9 = 84 14x = 84 Divide each side by '14'. x = 6 Simplifying x = 6
| 2(2y+4)+4=3(3y+4)-16 | | 20-x=2(x+1) | | 15x^2+2x-24=0 | | 2(2y-4)+5=4(4y-3)+10 | | 20x-26x+8=0 | | x+(x+1)=85 | | 7(y-2)=2y-39 | | x+17+3x=-27-3x-33 | | 17-5x=8+4x | | 21-44=3(x-1)-5 | | -7x-10(x+9)=-2(8x+8) | | 2z=17-21 | | 3(3y-3)-17=6(4y+1)-16 | | 8r+4=76 | | -2-7=-8+x | | 2x+4+x-7=3(x-7) | | x*x=45 | | 2y^2+11y=-5 | | 2160=180(n-2) | | 4(2z-3)=7(z+3) | | -5d-3.3=7.2 | | x*x*x=45 | | 3(4x-3)=63 | | 16+6y=82 | | 2x^2+4=x-6 | | 12x-8=24 | | 8x+12=132 | | 2x(x+6)+2x= | | 2a(a+5)= | | 3(a-2c)= | | 8x+4-2x=22 | | 23-x=x^2 |